EVALUASI USABILITY FITUR SCREEN TIME BREAKS DAN SLEEP REMINDERS PADA TIKTOK UNTUK ETIKA KESEJAHTERAAN DIGITAL - Ziezou Claudi Putri Dewi; Evy Nurmiati (CV. Denasya Smart Publisher, 2026)
The rapid growth of social media, particularly TikTok, has raised significant concerns regarding addictive behavior and the digital wellbeing of its users. In response, TikTok has introduced